Numerical Energy Storage Efficiency of MWCNTs-Propylene Glycol by Inducing Thermal Radiations and Combined Convection Effects in the Constitutive Model - Adnan,; Ashraf, Waqas; Khan, Ilyas; Shemseldin, Mohamed A.; Mousa, Abd Allah A. (Frontiers in Chemistry, 2022)
The study in organized for MWCNTs-PG nanofluid with uniform dispersion of MWCNTs in PG. It is assumed that both MWCNTs and PG thermally in equilibrium and no slip occurs between them. The MWCNTs suspended in PG uniformly and playing significant role. Firstly, the problem is formulated by utilizing empirical correlations, thermophysical attributes and similarity equations. Then the model is treated numerically along with coupling of shooting algorithm. The results against the pertinent flow quantities plotted and provided a comprehensive discussion against them. It is investigated that MWCNTs-PG has high thermal storage characteristics under the effects of thermal radiations and combined convection effects. Due to their high energy storage capability, these fluids will reliable for industrial applications.